Thermal Decomposition Studied of Some Polymeric Complexes - Aswar, A.S.; Bhave, N.S. (Asian Journal of Chemistry, 2010)
The thermal analysis of Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) chelates with 4,4´-dihydroxy-3-3´-diacetyl biphenyl-2-mercapto- 4,6-diamino triazine has been carried out in air atmosphere. All chelates show somewhat similar TG patterns. The activation energies of the chelates were calculated by using both the freeman-Carrol and Sharp-Wentworth methods. Various thermodynamic parameters have been evaluated by using thermal data The order of thermal stability of chelates is found to Cu(II) > Co(II) > Ni(II) > Fe(II) > Mn(II).